Modeling Dividend Behavior in Pakistan - Haleem, Fazli (Information Management and Business Review, 2011)
This study examines the determinants of dividend policy by Lintner (1956) and Braittan (1966) and their extended versions to examine their relative significance in the Pakistani context. The sample consists of thirty-five firms in the overall manufacturing sector and three sub-sectors: textile, energy and chemicals the period 2007 to 2009. The analysis reveals that Lintner model is better than other models examined in the study and net profit and lag dividends are important determinants of dividend policy in Pakistani manufacturing sector. The depreciation and liquidity has significant impact on the dividend policy when included in the Lintner model while investment demand, interest rate, share price behavior and debt turn out to be insignificant. The results imply that for dividend decisions, past dividends, profits and depreciation matters and Lintner model fits the data well in case of manufacturing sector of Pakistan.